Characterization of the mitochondrion genome of a Chlorella vulgaris strain isolated from rubber processing wastewater. Issue 3 (2nd July 2020) - Hu, Xiaowen; Tan, Deguan; Fu, Lili; Sun, Xuepiao; Zhang, Jiaming
Abstract: Chlorella vulgaris ITBBA3-12 was isolated from the rubber processing wastewater and has a role in wastewater purification. Its complete mitogenome contains 88754 bp, with a G + C content of 29.7%. A total of 64 genes were annotated, including 34 protein-coding genes, 27 tRNA genes, three rRNA (rrn23, rrn16, and rrn5). Phylogenetic analysis using the mitogenomes of Trebouxiophyceae species indicated that the strain ITBBA3-12 is closely related to C. vulgaris strain UTEX259 and NJ-7, and they clustered in the Chlorella lineage.